(untitled) (Eurasian Journal of Ecology, 2016)
Article contains results of researches of an ecological situation of the green space of the city on the basis of system methodology. The scheme which reflects ideas of structure and features of functioning of the system possessing high degree of complexity is as a result created. The object of research is “Chernyaevsky forest” in Perm. The contribution of technogenic, abiotic and biotic factors to formation of forest-park landscapes is considered. As result – territory zoning on intensity of an ecological situation.